NAuRA: Genomic Tool to Identify Staphylococcal Enterotoxins in Staphylococcus aureus Strains Responsible for FoodBorne Outbreaks - Merda, Déborah; Felten, Arnaud; Vingadassalon, Noémie; Denayer, Sarah; Titouche, Yacine; Decastelli, Lucia; Hickey, Bernadette; Kourtis, Christos; Daskalov, Hristo; Mistou, Michel-Yves; Hennekinne, Jacques-Antoine (Frontiers in Microbiology, 2020)
Food contamination by staphylococcal enterotoxins (SEs) is responsible for many food poisoning outbreaks (FPOs) each year, and they represent the third leading cause of FPOs in Europe. SEs are a protein family composed of 27 SEs. However, enzyme immunoassays can detect only the five classical SEs (SEA-SEE) directly in food. Thus, molecular characterization methods of strains found in food are now used for FPO investigations. Here, we describe on the development and implementation of a genomic analysis tool called NAuRA (Nice automatic Research of alleles) that can detect the presence of 27 SEs genes in just one analysis, and create a database of allelic data and protein variants for harmonizing analyses. This tool uses genome assembly data and the 27 protein sequences of SEs to detect. To include the different divergence levels between SE-coding genes, parameters of coverage and identity were generated from 10,000 simulations and a dataset of 244 assembled genomes from strains responsible for outbreaks in Europe as well as the RefSeq reference database. Based on phylogenetic inference performed using maximum-likelihood on the core genomes of the strains in this collection, we demonstrated that strains responsible for FPOs are distributed throughout the phylogenetic tree. Moreover, 71 toxin profiles were obtained using the NAuRA pipeline and these profiles do not follow the evolutionary history of strains. This study shows a pioneering method to investigate strains isolated from food at the genomic level and to analyze the diversity of all 27 SE-coding genes together.